Prevalence of Thyroid Cancer In Patients With Nodular Goiter and an Initial Benign Fine-Needle Aspiration Biopsy - Fassi, Juliana; Carrizo, Carolina; Bosco, María B.; Jaen, Ana V.; Russo Picasso, María F. (Revista del Hospital Italiano de Buenos Aires, 2024)
Introduction: Nodular goiter is a common condition, with fine-needle aspiration biopsy (FNAB) beinga fundamental tool for diagnosis. Although false negatives in cytology are very low (less than 3%), we suggest ongoing monitoring of nodules via ultrasound and potential repeat biopsy. This study aims to estimate the prevalence of thyroid cancer in patients with initially benign FNAB.Materials and Methods: Retrospective observational cohort study. Patients over 18 years old evaluatedat the outpatient clinics of the Endocrinology and Nuclear Medicine Service of a private communityhospital in the City of Buenos Aires were included. They had thyroid nodules with initially benign fine-needle aspiration biopsy performed between 1/2/2008 and 31/12/2012 and underwent repeat biopsy during a follow-up period of more than one year. All patients who underwent surgery during the followup period were recorded (reason for surgery and histology).Results: A total of 536 patients (383 women) with a mean age of 64.5 ± 12.5 years were included. Therewere 160 (29.85%) solitary nodules, measuring 19.9 ± 9.2 mm, with 203 (37.8%) patients exhibiting a cystic component. Forty-six patients underwent surgery, with 25 due to a second malignancy or suspicious finding on biopsy, 16 due to nodule size, three due to hyperthyroidism, and two due to  concurrent hyperparathyroidism. We found thyroid cancer in 16 patients, with 11 occurring in the biopsied nodules and five discovered incidentally during surgery for other reasons. The prevalence of malignancy by biopsy (11/536) was 2% (95% CI 1-4%), while the overall malignancy prevalence was 3% (95% CI 2-5%). Among the 11 patients with false negatives from the initial biopsy, 7 underwent repeat biopsy due to increased size or suspicious features, and 4 for surveillance purposes. All had low stages and favorable outcomes, except for one patient who presented with papillary carcinoma, a high cellvariant. The five patients with carcinomas found during surgery had papillary microcarcinomas.Conclusion: In our population, we found a low prevalence of false negatives in biopsy results among patients with nodular goiter.
Keywords: nodular goiter; thyroid; thyroid cancer; fine needle puncture